2010
DOI: 10.1051/fruits/2010031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest date and ripening degree on quality and shelf life of Hass avocado in Mexico

Abstract: -Introduction. Canada is an important avocado importer from Mexico. For most of the harvest season, fruit reach adequate pulp dry matter content, ripen properly and, consequently, quality and shelf life are excellent. However, after January, fruit dry matter content increases and blackened skin occurs. Shipments to Canada containing blackened fruit are rejected because this characteristic is wrongly associated with low pulp firmness and short shelf life. The objective of our research was to determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…2 Thai Customs Department, Import-Export Statistics, http://www.customs.go.th/Statistic/StatisticResult2550.jsp?page=1&statType =export&month=12&year=2010&product-CodeCheck=Y&productCode=08054000001 &countryCheck=null&country=, consulted on 11 August 2011. they have implications for fruit handling and the design of processing equipment. In addition, the color properties of the rind, the texture of the internal flesh and certain other internal characteristics, such as the soluble solids content, acidity and the ratio of soluble solids to acidity, which is a measurement of the quality or flavor index of citrus fruits, were also assessed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Thai Customs Department, Import-Export Statistics, http://www.customs.go.th/Statistic/StatisticResult2550.jsp?page=1&statType =export&month=12&year=2010&product-CodeCheck=Y&productCode=08054000001 &countryCheck=null&country=, consulted on 11 August 2011. they have implications for fruit handling and the design of processing equipment. In addition, the color properties of the rind, the texture of the internal flesh and certain other internal characteristics, such as the soluble solids content, acidity and the ratio of soluble solids to acidity, which is a measurement of the quality or flavor index of citrus fruits, were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Thailand, for example, currently exports pomelo to countries in Asia (China, Hong Kong, Singapore, Malaysia, Indonesia, Laos, Vietnam and Myanmar), Western Asia (Iran, United Arab Emirates and Saudi Arabia) and Europe (Norway, the Netherlands, the United Kingdom and Switzerland), as well as the United States and Canada. In 2010, the exported quantity was 12,149,126 kg (129,464,307 Baht/4.3 million US$) 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En ambos cultivares de aguacate el cambio de color de la piel fue observado en todos los frutos a partir del muestreo del 12 de julio de 2012 (Cuadro 3). Además, todos los frutos alcanzaron la madurez de consumo entre 8 y 12 d después de la cosecha, lo cual fue similar a lo encontrado para Hass por Osuna-García et al (2010). Sin embargo, esto no ocurrió en fechas de muestreo anteriores (Cuadro 3), lo que indica que los procesos fisiológicos para alcanzar la madurez de consumo ocurren de forma similar a Hass (Cox et al, 2004).…”
Section: Resultados Y Discusión Estudio 1 Madurez De Cosechaunclassified
“…Avocado (Persea americana Mill.) is an oleaginous fruit with high concentrations of monounsaturated fatty acids [3,4]. Previous studies showed that its fruits are a rich source of carotenoids, B group vitamins, ascorbic acid and tocopherols, and phenols [5][6][7].…”
Section: Introductionmentioning
confidence: 99%